Алгоритмічні методи визначення лінійних прискорень у реальному часі - Безвесільна, О. М.; Подчашинський, Ю. О. (НТУ "ХПІ", 2010)
В статье рассмотрены алгоритмические методы высокоточного определения линейных ускорений в реальном времени. Основой этих методов является идентификация вектора состояния чувствительного элемента в измерителях ускорений. Предложено использовать искусственную нейронную сеть для повышения точности измерений в нестационарных и неблагоприятных условиях.

In the article the algorithmic methods of high-precision definition of linear accelerations in realtime are considered. The basis of these methods is the identification of state vector of a sensing element in accelerometers. It is offered to use artificial neural network for increase of accuracy of measurements in non-stationary and unfavorable conditions.
Keywords: чутливий елемент; алгоритмічні методи; фільтр Калмана; нейрона мережа; measurement of accelerations; state vector; neural network